4-Aminophenyl acetamides and propanamides as potent transient receptor potential vanilloid 1 (TRPV1) ligands. Issue 15 (15th August 2018) - Kim, Changhoon; Ann, Jihyae; Lee, Sunho; Kim, Eunhye; Choi, Sun; Blumberg, Peter M.; Frank-Foltyn, Robert; Bahrenberg, Gregor; Stockhausen, Hannelore; Christoph, Thomas; Lee, Jeewoo
Graphical abstract: Abstract: A series of 2-(3, 5-substituted 4-aminophenyl)acetamide and propanamide derivatives were investigated as human TRPV1 antagonists. The analysis of the structure-activity relationship indicated that 2-(3, 5-dihalo 4-aminophenyl)acetamide analogues displayed excellent antagonism of h TRPV1 activation by capsaicin and showed improved potency compared to the corresponding propanamides. The most potent antagonist (36 ) exhibited potent and selective antagonism for h TRPV1 not only to capsaicin but also to NADA and elevated temperature; however, it only displayed weak antagonism to low pH. Further studies indicated that oral administration of antagonist36 blocked the hypothermic effect of capsaicin in vivo but demonstrated hyperthermia at that dose. A docking study of36 was performed in our established h TRPV1 homology model to understand its binding interactions with the receptor and to compare with that of previous antagonist1 .